Household Water Purification: A Community Transformation Experience - Navas Gotopo, Soreiret Margarita; Navas Gotopo, Soratna Veronica; Peña Colina, Katiusca Josefina; Pineda Franco, Carla Rosario; Ramírez Sáenz Soto, Carmen; Arana Meza, Luis Pompeyo; Pecho Rivera, María Cristina (LACCEI, 2025)
This study presents the results of an initiative aimed at improving household water purification in the community of “La Negrita” (Falcón, Venezuela). The core issue was identified through a participatory diagnostic process with key informants, who voiced concerns about the quality of the supplied water. The research followed a mixed-methods approach with a qualitative emphasis, grounded in the socio-critical paradigm and framed within the participatory action research methodology. It was conducted as a cross-sectional field study that involved both community members and the research team. The problematic situation was identified through lived experience, followed by the proposal of alternative solutions and the implementation of an action plan that led to a water disinfection method and guidance for its proper use. The techniques employed included participant observation, interviews, and physicochemical and microbiological analyses of water samples. These allowed for the identification of pathogenic agents and the classification of the water as type 1A, according to current regulations, making it suitable for treatment with sodium hypochlorite. This experience is considered a significant contribution to community health, as it led to a reduction in the microbial load of household drinking water.